THE EFFECT OF TURKISH OLIVE BRANCH OPERATION ON SYRIA’S NATIONAL SECURITY STABILITY IN 2018 - Zaklyyah Widad Zaenal (Mediasi: Journal of International Relations, 2020)
This paper explains how the Olive Branch Operation exerted influence on Syria's national security stability throughout 2018 using the concept of security stability incurred by Barry Buzan in analyzing the influences exerted by Olive Branch Operation. The method used in this study was a qualitative research method with analytical descriptive writing techniques. This research shows that the Olive Branch Operation conducted by Turkey exerts a negative influence on the stability of Syria's national security in 2018. It is based on several indicators in the military, political, economic, social, and environmental sectors. In addition, the results of this study also show that Turkey's actions to protect its territory are in accordance with Islamic teachings that allow carrying out attacks if attacked first. However, Islamic teachings have not been fully implemented in the Olive Branch Operation because there are still many adverse impacts on civilians who do not participate in the war.Keywords: Afrin; National Security; Olive Branch Operation; PYD-YPG; Turkey